The British Art Show : Old Allegiances and New Directions 1979-1984. - Ikon Gallery, Birmingham; Museum and Art Gallery, Birmingham; Royal Scottish Academy, Edinburgh; Mappin Art Gallery, Sheffield; Southampton Art Gallery, Southampton (London : Arts Council of Great Britain, 1984)
Art & Language ; Atherton, Kevin ; Atkinson, Terry ; Auerbach, Frank ; Ayres, Gillian ; Baer, Jo ; Robbins, Bruce ; Bailey, Peter ; Beattie, Basil ; Bellany, John ; Bevan, Tony ; Brisley, Stuart ; Burgin, Victor ; Bush, Paul ; Campbell, Steven ; Caro, Anthony ; Carter, John ; Carter, Tony ; Chadwick, Helen ; Chaimowicz, Marc ; Charlton, Alan ; Cragg, Tony ; Craig-Martin, Michael ; Davies, John ; Deacon, Richard ; Durward, Graham ; etc.
The British Art Show : Old Allegiances and New Directions 1979-1984, Museum and Art Gallery and Ikon Gallery, Birmingham, 2 November - 22 December 1984 / Royal Scottish Academy, Edinburgh, 19 January - 24 February 1985 / Mappin Art Gallery, Sheffield, 16 March - 4 May 1985 / Southampton Art Gallery, Southampton, 18 May - 30 June 1985
boek